Forestry and livestock make use of GIS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Geographical Information Systems (GIS) are now being brought into use in Africa having already proved their value in the North. Scientists in Mali are using a small scale GIS study to determine potential reserves of fuelwood in a forest in the...